2022
DOI: 10.1111/jfpp.16610
|View full text |Cite
|
Sign up to set email alerts
|

Thai traditional fermented fish paste Ka‐pi‐plaa : Chemical compositions and physical properties

Abstract: Fermentation plays an important role in food preservation as well as improvement of the nutritional and functional values of foods. For food rich in proteins, fermentation allows the cleavage of proteins by proteases to produce bioactive peptides, which substantially increase the biological properties of food (Steinkraus, 2002), and thus, fermented protein-enriched food products are good sources of peptides and amino acids for human consumption (Rajapakse et al., 2005). Fermentation of fish is the transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Shrimp paste is a highly appreciated traditional fermented condiment in China and other Southeast Asia regions relying on its unique avor, nutritional quality, and health-promoting properties. The research have indicated that shrimp paste is rich in functional components, including free amino acids, chitin, and other nutrients (Sripokar et al, 2022). Particularly, the shrimp paste is abundant in astaxanthin, a highly potent antioxidant known as super vitamin E, rendering it a valuable source of this essential nutrient (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Shrimp paste is a highly appreciated traditional fermented condiment in China and other Southeast Asia regions relying on its unique avor, nutritional quality, and health-promoting properties. The research have indicated that shrimp paste is rich in functional components, including free amino acids, chitin, and other nutrients (Sripokar et al, 2022). Particularly, the shrimp paste is abundant in astaxanthin, a highly potent antioxidant known as super vitamin E, rendering it a valuable source of this essential nutrient (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%